Application of total quality management techniques to safety analysis in software product development. (1st January 2001) - Moynihan, Gary P.; Ray, Paul S.; Batson, Robert G.; Nichols, William G.
The safety level of any system may be defined as the probability that no catastrophic accident is expected to occur during system operation, for a specified period of time. The purpose of software safety analysis is to reduce system risk, due to software malfunctions, to an acceptable level. Conventional software safety analysis techniques are reactive in orientation. They are intended to identify software faults as part of a post-programming evaluation procedure. A more cost-effective approach would be to avoid introducing the faults into the computer code. This paper discusses the ongoing establishment of a development methodology that would incorporate this proactive approach to software safety analysis, by applying the concepts of total quality management. This research provides a linkage of software engineering to such classical industrial engineering activities as safety analysis and quality control.